Luqman's advice to his son - Khan, Saniyasnain; Sarkar, Ramendranath (Goodword Books New Delhi, 2003)
Advice to His Son is a poignant and timeless narrative that encapsulates a father's wisdom and life lessons, offering guidance on values such as integrity, perseverance, and the importance of making thoughtful choices.